APLIKASI SIMULASI E-VOTING PEMILIHAN KETUA HIMPUNAN SISTEM INFORMASI ISTN DENGAN OTENTIKASI FACE RECOGNITION MENGGUNAKAN METODE LBPHFACES - Sandy Aprianto Saputra; Marhaeni Marhaeni (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2020)
The process of selecting the Leader of the ISTN Information System Association is through general elections where the implementation is still manual which results in inefficient because it takes a lot of time, space and costs. In order to run elections more efficiently, e-voting is the best way to carry out the election and implement the system using a web-based computer so that it is guaranteed in terms of speed and data processing. In this study, face recognition with the lbphface method was chosen as an additional security so that web-based selection is guaranteed security. The results of the election will be immediately known because the calculations are carried out automatically by the computer system and can be seen by the admin.